Painting a hat, Nakoaktok - Curtis, Edward S., 1868-1952
The painter is clad in a short, seamless, cedar-bark cafe, which is worn for protection from rain. That she is a woman of wealth and rank is shown by the abalone-shell nose-ornament and the gold bracelets, no less than by her possession of a "chief's hat." These waterproof hats, of a form borrowed from the Haida, are made of closely woven shreds of fibrous spruce-roots, and are ornamented with one of the owner's crests- a highly conventionalized painting of some animal or mythological being.